Pulse Width Prediction Control Technique Applied to a Half-Bridge Boost - Bayona, Jhon Fredy; Guarnizo, Jose; Gelvez, Nancy (TECCIENCIA, 2018)
The pulse width prediction control technique has been widely used in AC-DC converters with power factor correction in boost topology, where satisfactory results have been reported without the need to use classic control laws. However, this technique has not been explored for other types of ACDC converters with power factor correction. In this work, the use of this technique is proposed in an AC-DC converter with power factor correction in a half-bridge boost topology. This topology presents high efficiency because it uses the least number of semiconductors compared to other topologies. In this technique the duty cycle is predicted by processing the average values of state and input variables of the converter in half bridge boost topology, using only four multiplications and five additions, which implies less complexity in its implementation. For its validation simulations were performed using MATLAB R Simulink, where it was possible to observe values of power factor and THD comparable with other control methods such as non-linear carrier control, and conventional analog control, both reported in the literature.